1.) 3x - 4y = -5 . . . (1)
-x + 2y = 3 . . . (2)
Make the coeficient of one of the variables equal. We make the coeficient of y equal by multiplying (2) by 2.
(2) x 2 => -2x + 4y = 6 . . . (3)
Eliminate the variable by subtracting (if the signs are the same) or adding (if they have different signs), here the coefitient of y in (1) and (3) are the same but have different signs, so we add.
(1) + (3) => x = 1
Substituting x = 1 into any ot the equations gives you the value of y, we substitute into equation (2).
-1 + 2y = 3
2y = 3 + 1 = 4
y = 4/2 = 2
Writing the answer in the form of (x, y), we have (1, 2).